KESAN BULI SIBER DALAM KALANGAN PELAJAR KOLEJ UNIVERSITI ISLAM MELAKA (KUIM) - Mustaffa, Fazurah; Shaban, Siti Haziqah (Jurnal 'Ulwan, 2023)
The Internet and various digital devices have become an integral part of society’s life for a variety of purposes and functions. Therefore, internet users are also vulnerable to cyber bullying directly or indirectly, especially to KUIM students. Therefore, this study aims to look at the effects of cyber bullying among KUIM students. The design of the study is quantitative in the form of a survey conducted on KUIM students by using a cyber bullying questionnaire to obtain information related to the relationship of cyber bullying behavior based on emotional, physical and attitude aspects. The respondents of the study involved were a total of 110 KUIM students from various ages, semesters and study programs. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 22. The results of the study found that there is a significant relationship between cyberbullying with emotional aspects among students at KUIM, (r = .685, k